Influence Of Product Quality On Company Image In PT. The Eternal Holy Mountain Of Medan - Ingatan Laia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat-Universitas Darma Agung. (LPPM_UDA), 2022)
Product quality is the overall characteristics and characteristics of service products that support the ability to satisfy needs. Meanwhile, corporate image is the impression, feeling, image of the community or the public towards the company, an impression that is intentionally created from a product or service offered. The formulation of the problem in this study is